Adaptation of ACMG/AMP guidelines for standardized variant interpretation in familial hypercholesterolemia - Iacocca, Michael A. (2019)
Background: The successes of clinical genetics rely on accurate DNA variant interpretation for the purpose of informing diagnosis and treatment; However, this practice is often rudimentary and differs among diagnostic laboratories, leading to inconsistencies in pathogenicity classification: In response, the Clinical Genome (ClinGen) Resource consortium approves expert panels to recommend disease-specific guidelines to achieve evidence-based, standardized variant curation practice.